Moral Status (in the works of the expert Javadi Amuli) - Ali Pakpoor (حکمت اسرا)
The moral status of beings is an important discussion in moral philosophy and is nowadays being attended to from different aspects. Moral status denotes the very status which makes beings responsible. And as well, many theories have been presented on its limits and criteria. The most important theories related to this discussion are as follows: The theory of genetic humanity, with the criteria of ‘’ humane existence’’; the theory of moral agency, with the criteria of ‘’ moral agent’’; perception-center theory, with the criteria of ‘’ perceiving being’’;  the theory of organic life, with the criteria of ‘’ living being’’; the theory of deep ecology, with the criteria of ‘’ the beings of the biosphere’’;  the theory of foundation relation, with the criteria of ‘’a being possessing  either social relationships or ecological ones’’. Based on the available theories, and as well, the expert Javadi Amuli’s works and views, the present paper seeks to introduce the criteria of ‘’ existence’’ as the minimum requirement of being’s moral status; and also, based on the existential gradation, it seeks to discuss and reach conclusion on the  gradational nature of beings’ moral status. It appears that the limit of the moral status in this view is much extended. On the one hand, it encompasses human beings, and far superior, God and the angelic, and on the other hand, from an inferior position, it encompasses animals and even plants and in a mystical interpretation, all beings.